Biomass to biofuels - Syngellakis, S. (WIT Press, 2015)
Biomass is a continuously renewed source of energy formed from or by a wide variety of living organisms. Through biochemical and thermochemical processes, it is converted into gaseous, liquid or solid biofuels, which already meet a significant share of the current world energy needs. Because of their contribution to the sustainability of energy supply, reduction of green house gas emissions as well as local employment and energy self-reliance, research interest and activity in enhancing biofuel energy output, efficiency and performance remain strong. The first part of this volume comprises five articles mainly concerned with biomass resource potential and management. The emphasis in the subsequent group of eleven articles is on biomass conversion processes, aiming at assessing performance as well as output quality and diversity. Biodiesel, a fluid biofuel produced from biomass with high lipids such as rapeseed oil, sunflowers and soy beans, is the focus of two articles: the first investigates the effect of biodiesel blending with diesel fuel on diesel engine performance and emissions, the second assesses the efficiency of catalytic reforming of biodiesel into a gaseous mixture, used directly as Solid Oxide Fuel Cell (SOFC) fuel. In the last three articles, the prospects of biofuels as viable sources of energy are examined within European contexts. This volume addresses a significant number of important themes and thus combines subject breadth and density with in-depth study of biomass resourcing and processing as well as the issue of biofuel and renewable energy sustainability.